Local climatic conditions constrain soil yeast diversity patterns in Mediterranean forests, woodlands and scrub biome. Issue 1 (13th November 2015) - Yurkov, Andrey M.; Röhl, Oliver; Pontes, Ana; Carvalho, Cláudia; Maldonado, Cristina; Sampaio, José Paulo
Abstract : Soil yeasts represent a poorly known fraction of the soil microbiome due to limited ecological surveys. Here, we provide the first comprehensive inventory of cultivable soil yeasts in a Mediterranean ecosystem, which is the leading biodiversity hotspot for vascular plants and vertebrates in Europe. We isolated and identified soil yeasts from forested sites of Serra da Arrábida Natural Park (Portugal), representing the Mediterranean forests, woodlands and scrub biome. Both cultivation experiments and the subsequent species richness estimations suggest the highest species richness values reported to date, resulting in a total of 57 and 80 yeast taxa, respectively. These values far exceed those reported for other forest soils in Europe. Furthermore, we assessed the response of yeast diversity to microclimatic environmental factors in biotopes composed of the same plant species but showing a gradual change from humid broadleaf forests to dry maquis. We observed that forest properties constrained by precipitation level had strong impact on yeast diversity and on community structure and lower precipitation resulted in an increased number of rare species and decreased evenness values. In conclusion, the structure of soil yeast communities mirrors the environmental factors that affect aboveground phytocenoses, aboveground biomass and plant projective cover. Abstract : The authors provide the first comprehensive inventory of soil yeasts in a Mediterranean ecosystem and evaluate the effect of microclimate factors on yeast community in a transect from humid broadleaf forests to dry maquis. Abstract :